(untitled) (Management and Connections Journal, 2025)
Public-private partnerships (PPPs) can be seen as ways to enable the implementation of high-impact projects for society. Therefore, the objective of this study was to analyze the criteria for PPPs to enable innovation in public policies. To achieve this, we decided to carry out a case study of a pioneering partnership in Brazil: the PPP on the Rota dos Coqueiros highway, in Pernambuco. As a result, it was observed that the adequate allocation of risks between partners, the existence of a robust regulatory framework and government involvement, offering guarantees, are among the main elements that guarantee the success of a PPP. However, it was concluded that PPPs do not preclude effective action by the Public Power in monitoring the application of resources, given that the State continues to be the main responsible for guaranteeing public services provided to society.